Analisis Penentuan Harga Jual Dengan Metode Variable Costing dan Activity Based Costing Bakso BG Laka Laka: Analysis of Selling Price Determination Using Variable Costing and Activity Based Costing Methods for BG Laka Laka Meatballs - Shafiliah Sany; Amanda Putri Farahdillah; Amanda Agusari; Risma Andini (CV Warnak Johanna Nusantara, 2025)
This article analyzes the calculation using variable costing and activity based costing methods on the selling price of products at Bakso BG Laka-Laka UMKM. This study uses descriptive qualitative data collection methodology and techniques, focusing on data and information from the owner of Bakso BG Laka-Laka UMKM, using journals as references, and documentation as research documents. The results of the study indicate that activity based costing is more accurate than variable costing, because activity based costing provides a more comprehensive approach by adjusting raw material costs based on business activities, while variable costing only focuses on direct production costs. This study recommends the most efficient and effective method for determining product selling prices, increasing the efficiency of price measurement and business profitability. In addition, it also functions as a reference for other UMKM actors in making the right decisions regarding product selling prices